Bending behaviour of timber beams strengthened with glass fibre reinforced polymer (GFRP) - Erma Suryati Sabariah, Md Ali (2014)
This researched was conducted to investigate the bending behavior of the timber beams when strengthened with Glass Fiber Reinforced Polymer (GFRP) sheets. There are three timber beams of Keruing species with the dimensions of 100 x 100 x 1500 mm was tested. Two of the beams was strengthened before tested to failure under three point loading test, while one are used as a control beam (unstrengthen). The deflection was measured using Linear Variable Displacement Transducer (LVDT). The damaged beams was repaired by increasing the thickness of GFRP sheets to 1 Onim and tested using the same testing procedure. The failure modes also have been identified through the experiment. The beams are categorized as under-reinforced and over-reinforced based on the modes of failure in members. From the results, it shows that the beams strengthened with GFRP performed better result compared to control beam. The using of proposed experimental technique increased the ultimate load between 12 - 40% for the strengthened beams when compared to the control beam and decreased 10% of the specimen's deflection. Based on experimental results also, the repaired damaged beams can resist load up to 83% of the damaged beams. From the research findings, it shows that the use of GFRP sheets can decrease the effect of local defects in the timber and the bending strength of the members can be increased. The GFRP sheets are one of the reinforcement materials which have a good potential to be utilized in the new building structure or rehabilitation works of timber structures.